Systems thinking for health emergencies: use of process mapping during outbreak response - Ambrose Talisuna; Mamadou Harouna Djingarey; Pierre Formenty; Adesola Yinka-Ogunleye; Chikwe Ihekweazu; Kara N Durski; Michael Osterholm; Ibrahim Mamadu; Sylvie Briand; Ibrahima-Soce Fall; Amara Jambai; Dhamari Naidoo; et al. (BMJ Global Health)
Process mapping is a systems thinking approach used to understand, analyse and optimise processes within complex systems. We aim to demonstrate how this methodology can be applied during disease outbreaks to strengthen response and health systems. Process mapping exercises were conducted during three unique emerging disease outbreak contexts with different: mode of transmission, size, and health system infrastructure. System functioning improved considerably in each country. In Sierra Leone, laboratory testing was accelerated from 6 days to within 24 hours. In the Democratic Republic of Congo, time to suspected case notification reduced from 7 to 3 days. In Nigeria, key data reached the national level in 48 hours instead of 5 days. Our research shows that despite the chaos and complexities associated with emerging pathogen outbreaks, the implementation of a process mapping exercise can address immediate response priorities while simultaneously strengthening components of a health system.